Digital Innovations for Sustainable Forest Management: A Review of Strategies and Applications in the Nigerian Context (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
The sustainable management of forest resources is imperative for environmental preservation and societal well-being, particularly, for countries like Nigeria facing significant challenges in resource governance. Traditional approaches have proven inadequate in addressing issues such as deforestation, illegal logging, and insufficient monitoring and enforcement. In response, the integration of digital tools present promising solutions to enhance forest resource management in Nigeria. Digital technologies, including satellite monitoring, remote sensing, GIS, and big data analytics offer opportunities for real-time data driven decision-making and improved governance. By adopting digital strategies, Nigeria can address forestrelated challenges, combat illegal activities, and promote large-scale forest restoration and reforestation initiatives. Thus, integrated land use planning, supported by digital tools, fosters sustainable development by balancing conservation objectives with economic growth.
Keywords: Digital Technologies; Environmental Management; Forestry Management; Sustainable Forest